Conflits et stratégies d’acceptabilité sociale autour des énergies marines renouvelables sur le littoral français - Annaig Oiry (VertigO)
The ocean provides an important source of potential renewable energy resources and France has marine territory that is particularly conductive to the development of offshore wind energy and tidal energy. However, in coastal areas, a lot of human conflicts arise from numerous uses that may be antagonistic: in addition to "traditional" activities (tourism, commercial fishing, etc.) have been superimposed the intensification of certain practices (extraction of marine aggregates) or new activities (marine renewable energies, offshore aquaculture, etc.) This article stresses on relationships between uses conflicts and acceptability strategies which are developed by project leaders concerning marine renewable energies. In particular, the social acceptability of these energies involves questions about consultation meetings or compensation for stakeholders who perceive some of their interests to be modified.